Towards inclusive funding practices for early career researchers - de Winde, Charlotte M. (2021)
Securing research funding is a challenge faced by most scientists in academic institutions worldwide. Funding success rates for all career stages are low, but the burden falls most heavily on early career researchers (ECRs). These are young investigators in training and new principal investigators who have a shorter track record. ECRs are dependent on funding to establish their academic careers. The low number of career development awards and the lack of sustained research funding result in the loss of ECR talent in academia. Several steps in the current funding process, from grant conditions to review, play significant roles in the distribution of funds. Furthermore, there is an imbalance where certain research disciplines and labs of influential researchers receive more funding. As a group of ECRs with global representation, we examined funding practices, barriers, and facilitators to the current funding systems. We also identified alternatives to the most common funding distribution practices, such as diversifying risk or awarding grants on a partly random basis. Here, we detail recommendations for funding agencies and grant reviewers to improve ECR funding prospects worldwide and promote a fairer and more inclusive funding landscape for ECRs.